CAP protein superfamily members in Toxocara canis. Issue 1 (December 2016) - Stroehlein, Andreas; Young, Neil; Hall, Ross; Korhonen, Pasi; Hofmann, Andreas; Sternberg, Paul; Jabbar, Abdul; Gasser, Robin
Abstract Background Proteins of the cysteine-rich secretory proteins, antigen 5 and pathogenesis-related 1 (CAP) superfamily are recognized or proposed to play roles in parasite development and reproduction, and in modulating host immune attack and infection processes. However, little is known about these proteins for most parasites. Results In the present study, we explored CAP proteins ofToxocara canis, a socioeconomically important zoonotic roundworm. To do this, we mined and curated transcriptomic and genomic data, predicted and curated full-length protein sequences (n = 28), conducted analyses of these data and studied the transcription of respective genes in different developmental stages ofT. canis . In addition, based on information available forCaenorhabditis elegans, we inferred that selected genes (includinglon-1, vap-1, vap-2, scl-1, scl-8 andscl-11 orthologs) ofT. canis and their interaction partners likely play central roles in this parasite's development and/or reproduction via TGF-beta and/or insulin-like signaling pathways, or via host interactions. Conclusion In conclusion, this study could provide a foundation to guide future studies of CAP proteins ofT. canis and related parasites, and might assist in finding new interventions against diseases caused by these parasites.